2013
DOI: 10.1016/j.visres.2012.12.012
|View full text |Cite
|
Sign up to set email alerts
|

X-linked cone dystrophy and colour vision deficiency arising from a missense mutation in a hybrid L/M cone opsin gene

Abstract: In this report, we describe a male subject who presents with a complex phenotype of myopia associated with cone dysfunction and a protan vision deficiency. Retinal imaging demonstrates extensive cone disruption, including the presence of non-waveguiding cones, an overall thinning of the retina, and an irregular mottled appearance of the hyper reflective band associated with the inner segment ellipsoid portion of the photoreceptor. Mutation screening revealed a novel p.Glu41Lys missense mutation in a hybrid L/M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…One day, gene therapy methods may be sufficiently safe and practical that it will be possible to treat people for whom color blindness is a detriment to their quality of life. However, red-green color blindness can also be caused by point mutations in the cone opsin genes (Winderickx et al 1992;Neitz et al 2004;Carroll et al 2009Carroll et al , 2012Wagner-Schuman et al 2010), which in some cases are associated with cone dystrophy (Gardner et al 2010;McClements et al 2013), leading to debilitating vision loss in addition to color vision deficits. It remains to be seen whether the gene therapy approach used in squirrel monkeys could rescue cone dystrophy caused by mutations in cone photopigment genes.…”
Section: Discussionmentioning
confidence: 99%
“…One day, gene therapy methods may be sufficiently safe and practical that it will be possible to treat people for whom color blindness is a detriment to their quality of life. However, red-green color blindness can also be caused by point mutations in the cone opsin genes (Winderickx et al 1992;Neitz et al 2004;Carroll et al 2009Carroll et al , 2012Wagner-Schuman et al 2010), which in some cases are associated with cone dystrophy (Gardner et al 2010;McClements et al 2013), leading to debilitating vision loss in addition to color vision deficits. It remains to be seen whether the gene therapy approach used in squirrel monkeys could rescue cone dystrophy caused by mutations in cone photopigment genes.…”
Section: Discussionmentioning
confidence: 99%
“…The protan impairments are distinguished by an absence or anomaly of L-cone function, while deuteran defects are distinguished by an absence or abnormality of M-cone function. 12 Deuteranopia, green CB) or protanopia, red CB occurs as a result of absence of photo pigment of the green or red cone. However, when the photo pigment response of the green cones is shifted towards that of the red cones it becomes deuteranomaly which is mild green colorblindness and when the photo pigment response of the red cone is shifted towards that of green cone it becomes protanomaly which is mild red colorblindness.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Mutations and rearrangements in the genes encoding the long, middle, and short wavelength sensitive cone pigments are responsible for color vision deficiencies. 4 A recent study has revealed the missense mutation in a hybrid L/M cone opsin gene leading to X-linked cone dystrophy and color vision deficiency. 5 …”
Section: Introductionmentioning
confidence: 99%